Parent Perceptions of Changes in Child Physical Activity During COVID-19 Stay-At-Home Orders - Eyler, Amy A.; Schmidt, Laurel; Kepper, Maura; Mazzucca, Stephanie; Gilbert, Amanda; Beck, Alan (Frontiers in Public Health, 2021)
Purpose: The purpose of this study was to explore parent perceptions of changes in child physical activity during COVID-19 stay-at-home orders. Design: A cross-sectional study. Setting: The research team used social media, relevant organizations, and neighborhood groups to distribute the survey link in May and June of 2020. Subjects: A convenience sample of parents of children aged 5–12. Measures: Survey to assess parental perceptions of changes in children's physical activity before and during stay-at-home orders, and environmental and social barriers to physical activity. Analysis: Results were analyzed using descriptive statistics, bivariate comparisons, and multinomial-logistic regression models with covariates of environmental factors, social factors, and frequency of factors as barriers on association with perceived physical activity change. Results: Data from 245 parents were analyzed. A majority (63.7%) of parents reported a decrease in children's physical activity during stay-at-home orders. More parents indicated social barriers (e.g., lack of access to playmates) than environmental barriers (e.g., lack of access to neighborhood play spaces) to children's physical activity. In multivariate analyses, the odds of parents reporting decreased physical activity was greater for those reporting lack of playmates (OR = 4.72; 95% CI: 1.99–11.17) and lack of adult supervision (OR = 11.82; 95% CI: 2.48–56.28) as barriers. No environmental barriers were significantly associated with decreased children's physical activity. Conclusion: The unique aspects of the COVID-19 pandemic provide a natural experiment for developing social and environmental strategies to improve children's overall physical activity. Assessing parental perceptions is a way to inform these future efforts.